Colorectal Cancer Survival Trends in the United States From 1992 to 2018 Differ Among Persons From Five Racial and Ethnic Groups According to Stage at Diagnosis: A SEER-Based Study. (18th October 2022) - Pankratz, Vernon S.; Kanda, Deborah; Edwardson, Nicholas; English, Kevin; Adsul, Prajakta; Li, Yiting; Parasher, Gulshan; Mishra, Shiraz I.
Introduction: Survival following colorectal cancer (CRC) has improved in the US since 1975, but there is limited information on stage-specific survival trends among racial and ethnic subgroups. Objectives: The purpose of this study was to estimate and compare trends in 1- and 5-year CRC cause-specific survival in the United States by both stage and race/ethnicity. Methods: We performed a retrospective cohort study of individuals diagnosed with CRC using the 1992-2018 Surveillance, Epidemiology and End Results (SEER) database. We estimated and compared time trends in 1- and 5-year survival for CRC stage by race/ethnicity. Results: Data from 399 220 individuals diagnosed with CRC were available. There were significant differences in stage-specific 1-year survival trends by race and ethnicity. Differences were most notable for distant stage CRC: survival probabilities increased most consistently for non-Hispanic American Indian/Alaska Native (AIAN) and Black (NHB) persons, but their trend lines were lower than those of Hispanic, and non-Hispanic Asian/Pacific Islander (API) and White (NHW) persons, whose initially greater gains appear to be slowing. Although the data do not support significant racial/ethnic differences in 5-year CRC survival trends by stage, AIAN and NHB persons have the lowest average survival probabilities for multiple CRC stages, and no racial/ethnic group has 5-year survival probabilities above 20% for distant-stage CRC. Conclusion: Although there has been an overall improvement in adjusted CRC-specific survival probabilities since 1992, AIAN and NHB persons continue to experience worse prognosis than those of other races/ethnicities. This highlights the importance of reinvigorating efforts to understand the causes of mortality in CRC, including those which may differ according to an individual's race or ethnicity.